2009
DOI: 10.1111/j.1467-9280.2009.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinning Saints and Saintly Sinners

Abstract: The question of why people are motivated to act altruistically has been an important one for centuries, and across various disciplines. Drawing on previous research on moral regulation, we propose a framework suggesting that moral (or immoral) behavior can result from an internal balancing of moral self-worth and the cost inherent in altruistic behavior. In Experiment 1, participants were asked to write a self-relevant story containing words referring to either positive or negative traits. Participants who wro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
256
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 616 publications
(321 citation statements)
references
References 28 publications
12
256
2
1
Order By: Relevance
“…In both studies, we manipulated whether participants had a salient self as a moral versus an immoral person relying on an established priming procedure that asks participants to describe and recall a situation in which they acted in a moral (versus immoral) manner (see e.g., Aquino et al, 2009;Sachdeva et al, 2009). This allowed us to capture moral consistency (i.e., high levels of prosocial behavior when a self-definition as moral is salient) as well as moral compensation People need cognitive resources to override short-term, reactive impulses in order to proactively pursue high standards and desirable long-term goals (Baumeister, 2002;Fishbach, Friedman, & Kruglanski, 2003;Hofmann et al, 2009;Mischel, 1974).…”
Section: The Present Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In both studies, we manipulated whether participants had a salient self as a moral versus an immoral person relying on an established priming procedure that asks participants to describe and recall a situation in which they acted in a moral (versus immoral) manner (see e.g., Aquino et al, 2009;Sachdeva et al, 2009). This allowed us to capture moral consistency (i.e., high levels of prosocial behavior when a self-definition as moral is salient) as well as moral compensation People need cognitive resources to override short-term, reactive impulses in order to proactively pursue high standards and desirable long-term goals (Baumeister, 2002;Fishbach, Friedman, & Kruglanski, 2003;Hofmann et al, 2009;Mischel, 1974).…”
Section: The Present Studiesmentioning
confidence: 99%
“…Recently, researchers who are interested in behavioral ethics and moral psychology have started to study these moment-to-moment balancing acts between prosocial and self-interested behavior 1 . This research has revealed important roles for the self and selfregulation processes in shaping our moral behaviors (Aquino, Freeman, Reed, Lim, & Felps, 2009;Blasi, 1983;Sachdeva, Iliev, & Medin, 2009;Zhong, Liljenquist, & Cain, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We adapted methods that have been shown to influence one's moral identity (Reed, Aquino, & Levy, 2007;Sachdeva, Iliev, & Medin, 2009 desk, and letter. All participants were then asked to write a short story about themselves using the words they received.…”
Section: Methodsmentioning
confidence: 99%